Repositioning Linagliptin for the Mitigation of Cadmium-Induced Testicular Dysfunction in Rats: Targeting HMGB1/TLR4/NLRP3 Axis and Autophagy - Hany H. Arab; Alzahraa A. Elhemiely; Azza A. K. El-Sheikh; Hana J. Al Khabbaz; El-Shaimaa A. Arafa; Ahmed M. Ashour; Ahmed M. Kabel; Ahmed H. Eid (MDPI AG, 2022)
Cadmium, a ubiquitous environmental toxicant, disrupts testicular function and fertility. The dipeptidyl peptidase-4 inhibitor linagliptin has shown pronounced anti-inflammatory and anti-apoptotic features; however, its effects against cadmium-evoked testicular impairment have not been examined. Herein, the present study investigated targeting inflammation, apoptosis, and autophagy by linagliptin for potential modulation of cadmium-induced testicular dysfunction in rats. After 60 days of cadmium chloride administration (5 mg/kg/day, by gavage), testes, epididymis, and blood were collected for analysis. The present findings revealed that linagliptin improved the histopathological lesions, including spermatogenesis impairment and germ cell loss. Moreover, it improved sperm count/motility and serum testosterone. The favorable effects of linagliptin were mediated by curbing testicular inflammation seen by dampening of HMGB1/TLR4 pathway and associated lowering of nuclear NF-κBp65. In tandem, linagliptin suppressed the activation of NLRP3 inflammasome/caspase 1 axis with consequent lowering of the pro-inflammatory IL-1β and IL-18. Jointly, linagliptin attenuated testicular apoptotic responses seen by Bax downregulation, Bcl-2 upregulation, and suppressed caspase 3 activity. With respect to autophagy, linagliptin enhanced the testicular autophagy flux seen by lowered accumulation of p62 SQSTM1 alongside upregulation of Beclin 1. The observed autophagy stimulation was associated with elevated AMPK (Ser487) phosphorylation and lowered mTOR (Ser2448) phosphorylation, indicating AMPK/mTOR pathway activation. In conclusion, inhibition of testicular HMGB1/TLR4/NLRP3 pro-inflammatory axis and apoptosis alongside stimulation of autophagy were implicated in the favorable actions of linagliptin against cadmium-triggered testicular impairment.